Low-carbon olefin hydrated fiber membrane as well as preparation method and application thereof
By using a multi-layered low-carbon olefin hydration fiber membrane during low-carbon olefin hydration, the problems of poor contact and low selectivity of hydration are solved, and more efficient hydration reactions and lower olefin stacking losses are achieved.
Patent Information
- Application Number
- CN202311218055.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-20
AI Technical Summary
The problems of poor water olefin contact, excessive water olefin ratio and low selectivity of target products during the hydration process of low-carbon olefins.
A low-carbon olefin hydrated fiber membrane is used, which consists of a hollow fiber membrane matrix by sequentially coating a first silane layer, a first functional layer, a first olephilic layer and a second functional layer, and the mobility of the contact effect of the hydrene and the reaction balance are improved by the combination of these layers.
The contact effect of hydrene is improved, the movement of hydration balance is promoted, the overlap loss of olefins is reduced, and the selectivity of low-carbon alcohols is significantly improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of olefin hydration, and in particular to a low-carbon olefin hydration fiber membrane and a preparation method and application thereof. Background Art
[0002] Olefin hydration is one of the important organic reactions and can be used to prepare alcohols, such as sec-butyl alcohol, isopropyl alcohol, cyclohexanol, etc. sec-butyl alcohol can be used as a solvent in industry and mixed with methanol in a certain proportion as a component to increase the octane number of gasoline; it can also be used to produce mineral processing agents, herbicides, plasticizers, etc., but the most important application is the production of methyl ethyl ketone, which accounts for about 90% of its total consumption. Methyl ethyl ketone is an excellent organic solvent and organic synthetic raw material, widely used in oil refining, fuel, high-grade coatings, medicine and other fields.
[0003] Traditional olefin hydration generally adopts sulfuric acid indirect hydration method, which has serious equipment corrosion problems and waste acid treatment problems, and has gradually been replaced by catalytic direct hydration method. Catalytic direct hydration method generally uses solid acid catalyst to directly generate corresponding low-carbon alcohol from low-carbon olefins.
[0004] Patent application CN104039435A discloses an integrated membrane hydration reactor, which uses water to produce related alcohol products from olefins. The integrated membrane hydration reactor includes: a solid acid olefin hydration catalyst located in a production zone; and a hydrophilic membrane located in a separation zone, which can selectively pervaporate water in one direction under olefin hydration process conditions, and can prevent pervaporation of related alcohols and permeation of olefins. The production zone can effectively form a production zone product mixture formed by related alcohols and any unreacted water. The related separation zone can effectively form and produce related alcohol products and pervaporated water products from the production zone product mixture. The olefin hydration method for forming related alcohol products from olefins using water uses the integrated membrane hydration reactor under olefin hydration process conditions.
[0005] Patent application CN104039435A discloses a combination of a hydration catalytic bed and a pervaporation membrane. A water-alcohol mixture is formed by a conventional catalytic bed. Under relatively static conditions, a relatively high concentration of an alcohol-water emulsion will gradually be separated into an alcohol-rich layer and a water-rich layer. Subsequently, the pervaporation membrane is used to recover the unreacted water from the hydration reaction in the water-rich layer to obtain pure water, and the pure water is used to continuously carry out the current level hydration reaction or the lower level hydration reaction. A small amount of alcohol dissolved in the water-rich layer intercepted by the pervaporation membrane is continuously concentrated and precipitated into the alcohol-rich layer, and the alcohol in the alcohol-rich layer is continuously extracted from the alcohol pipeline to the outside of the system. The catalytic bed may not contact the pervaporation membrane, or it may contact it. When the catalytic bed contacts the pervaporation membrane, the catalytic bed may be arranged against the outer surface of the hollow membrane, or it may be filled in the inner cavity of the hollow membrane. The pervaporation membrane may be directly prepared from an inorganic material, a polymeric material, or an organic-inorganic composite material. Using pervaporation membranes to replace conventional distillation towers for dehydration, alcohols or alcohol concentrates and water are separated, and the alcohols of the reaction products are removed and water is recycled, thereby promoting the hydration equilibrium to move to the right. However, the catalytic hydration layer and the pervaporation membrane are a macroscopic combination. Although they have certain effects of water recovery, separation of alcohols, and promotion of equilibrium movement, they lack comprehensive microscopic affinity-repulsion treatment and modification of water, olefins, and alcohols involved in the hydration reaction. On the other hand, the catalytic layer and membrane separation need to be further integrated on a smaller scale to reduce the reactor volume and reduce the space occupied by industrial equipment. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of poor water-olefin contact, excessive water-olefin ratio and low selectivity of target products in the hydration process of low-carbon olefins in the prior art, and to provide a low-carbon olefin hydration fiber membrane and a preparation method and application thereof. The low-carbon olefin hydration fiber membrane can improve the contact effect of water and olefin, promote the movement of hydration equilibrium, and reduce the superposition loss of olefins.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a low-carbon olefin hydrated fiber membrane, wherein the low-carbon olefin hydrated fiber membrane comprises a hollow fiber membrane substrate, a first silane layer, a first functional layer and a first olefinic layer sequentially coated on the inner surface of the hollow fiber membrane substrate from the inside to the outside, and a second silane layer and a second functional layer sequentially coated on the outer surface of the hollow fiber membrane substrate from the inside to the outside; the first functional layer contains amide, phenoxy, sulfonic acid, phosphate, pyrrol and furan groups; the first olefinic layer contains phenoxy groups; the second functional layer contains amide, pyrrol and furan groups.
[0008] A second aspect of the present invention provides a method for preparing a low-carbon olefin hydrated fiber membrane, wherein the method comprises:
[0009] (1) performing a silanization treatment on the hollow fiber membrane substrate to obtain a silanized hollow fiber membrane;
[0010] (2) in the presence of a first functional component, subjecting the inner surface of the silanized hollow fiber membrane of step (1) to a first functional treatment, and then in the presence of a first enephilic component, subjecting the inner surface of the hollow fiber membrane after the first functional treatment to a first enephilic treatment to obtain a hollow fiber membrane after the first enephilic treatment;
[0011] (3) in the presence of a second functional component, subjecting the outer surface of the hollow fiber membrane after the first olefin treatment in step (2) to a second functional treatment to obtain a low-carbon olefin hydrate fiber membrane;
[0012] The first functional component contains an amide group, a phenoxy group, a sulfonic acid group, a phosphate group, a pyrrol group, and a furan group; the first enophilic component contains a phenoxy group; and the second functional component contains an amide group, a pyrrol group, and a furan group.
[0013] The third aspect of the present invention provides a use of the light olefin hydrated fiber membrane described in the first aspect or the light olefin hydrated fiber membrane prepared by the preparation method described in the second aspect in a light olefin hydration reaction.
[0014] The inventors of the present invention found in the process of studying the hydration of low-carbon olefins that the olefin hydration was catalyzed by solid acid catalysts such as existing strong acid resins and ZSM-5 molecular sieves, and the olefin single-pass conversion rate was significantly lower than the thermodynamic equilibrium conversion rate (generally 3-8%). Low-carbon olefins are generally insoluble in water, and even if the water content is excessive, the two are still incompatible. From the perspective of excessive reaction raw materials to further promote the hydration equilibrium to move to the right, the effect is not obvious, and only the dilution effect on the product low-carbon alcohol can be achieved. Solid acid catalysts have good water binding properties, but poor compatibility with olefins. Olefins are difficult to adsorb on the solid acid catalytic surface after water saturation, which causes double bonds to be difficult to be activated. In order to improve the catalytic effect of solid acid, solid acid modification is mainly carried out around the direction of increasing acid strength and acid density, but this direction can cause side reactions such as olefins to overlap, resulting in a reduction in low-carbon alcohol yield and selectivity.
[0015] The low-carbon olefin hydrated fiber membrane provided by the present invention, the first silane layer and the second silane layer can improve the stability of the subsequent first functional layer, the first olefinic layer and the second functional layer and extend the service life. The first functional layer, the first olefinic layer and the second functional layer solve the mass transfer problems, equilibrium promotion problems and product yield selectivity problems existing in the prior art from the microscopic mechanism, and improve the selectivity of the product.
[0016] The low-carbon olefin hydration fiber membrane provided by the present invention is not only applicable to olefin hydration reactions with an olefin content of more than 80%, but also applicable to olefin hydration reactions with a low-carbon olefin content of less than 80%, which greatly expands the material processable range of olefin hydration reactions and is particularly suitable for dilute olefin hydration situations. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] In the present invention, each group and its content in the first silane layer, the second silane layer, the first functional layer, the first enophilic layer and the second functional layer are measured by infrared spectroscopy. The specific test conditions are KBr tableting at 400cm -1 -4000cm -1 The range is scanned and the group content in each layer is measured step by step during the preparation process.
[0019] In the present invention, the thicknesses of the first silane layer, the second silane layer, the first functional layer, the first enophilic layer and the second functional layer are all measured by an X-ray fluorescence thickness gauge.
[0020] The first aspect of the present invention provides a low-carbon olefin hydrated fiber membrane, wherein the low-carbon olefin hydrated fiber membrane comprises a hollow fiber membrane substrate, a first silane layer, a first functional layer and a first olefinic layer sequentially coated on the inner surface of the hollow fiber membrane substrate from the inside to the outside, and a second silane layer and a second functional layer sequentially coated on the outer surface of the hollow fiber membrane substrate from the inside to the outside; the first functional layer contains amide, phenoxy, sulfonic acid, phosphate, pyrrol and furan groups; the first olefinic layer contains phenoxy groups; the second functional layer contains amide, pyrrol and furan groups.
[0021] The inner surface of the hollow fiber membrane matrix is coated with a first functional layer and a first ene-philic layer. The first functional layer is the main site for olefin hydration reaction. This layer contains ene-philic groups (for enriching olefins), hydrophilic groups (for enriching water), catalytic groups (for activating olefins, and rationally regulating acid strength through coordinated group matching), and low-carbon alcohol repelling groups (for transferring the low-carbon alcohol generated by the reaction to the outside of the reaction system to promote the hydration reaction to move to the right).
[0022] By coating the first olefin-philic layer, olefins are enriched. The olefins enriched by the first olefin-philic layer react with the water transmitted through the pores of the hollow fiber membrane matrix on the inner side of the first olefin-philic layer (i.e., the first functional layer). Since the thickness of the reaction interface is small and the hydration exothermic thermal effect is limited, there will be no situation where the catalyst is sintered or deactivated due to temperature runaway. Since the acid strength of the reaction layer catalyst is moderate, it will not cause side reactions such as olefin superposition and low-carbon alcohol condensation, and the yield and selectivity of low-carbon alcohol are significantly improved; further, the first functional layer (reaction layer) contains low-carbon alcohol repelling groups, which can make the low-carbon alcohol produced by hydration gradually transfer to the water phase outside the matrix along the first functional layer and the matrix pores under the action of molecular forces, thereby promoting the hydration equilibrium to move continuously to the right.
[0023] By coating the second functional layer, which contains hydrophilic groups and low-carbon alcohol repelling groups, water is enriched on the outer surface and pores of the substrate through the hydrophilic groups, providing microscopic excess water for the hydration reaction. Due to the presence of hydrophilic groups, the macroscopic water-to-olefin ratio requirement of the membrane is significantly reduced, thereby significantly reducing the water circulation and separation load of the entire system; the low-carbon alcohol repelling groups in the first functional layer and the repelling groups in the second functional layer work together to continuously transfer the low-carbon alcohol produced by hydration from the reaction zone to the water phase.
[0024] In the present invention, the hollow fiber membrane substrate is a hollow cylinder with a hollow structure inside as conventionally defined in the art. The inner surface mentioned in the present invention refers to the inner surface of the hollow cylinder, and the outer surface mentioned in the present invention refers to the outer surface of the hollow cylinder.
[0025] In the present invention, there is no particular limitation on the type of the low-carbon olefin hydration fiber membrane. Preferably, the hollow fiber membrane substrate is a hollow ceramic fiber membrane.
[0026] In the present invention, there is no particular limitation on the properties of the hollow fiber membrane substrate. Preferably, the inner diameter of the hollow fiber membrane substrate is 0.1-0.5 mm, the outer diameter is 1.1-2.5 mm, the pore size of the fiber membrane wall is 30-80 nm, and the porosity is 40-60%.
[0027] In the present invention, there is no particular limitation on the material of the hollow fiber membrane substrate. Preferably, the material of the hollow fiber membrane substrate is silicon dioxide and / or aluminum oxide.
[0028] In the present invention, preferably, the thickness of the first silane layer and the second silane layer are independently 5-8 nm.
[0029] In the present invention, it can be understood that in the preparation process of the first silane layer and the second silane layer, the hollow fiber membrane substrate is immersed in a solution containing a silane component, and the inner and outer surfaces of the hollow fiber membrane are in contact with the silane component, and the thickness of the first silane layer and the second silane layer obtained are the same.
[0030] In the present invention, preferably, the first silane layer and the second silane layer are each independently provided by at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
[0031] In the present invention, preferably, based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of the amide group in the first functional layer is 10-17 mmol / m 2 , the content of phenoxy group is 9-16mmol / m 2 The content of sulfonic acid group is 16-30mmol / m 2 The content of phosphate group is 7-15mmol / m 2 The content of pyrrolyl is 18-26mmol / m 2 The furanyl content is 3-7mmol / m 2 The advantages of adopting this preferred embodiment are that the enrichment and activation of the reaction raw materials and the timely removal of the reaction products can be achieved.
[0032] In the present invention, preferably, the thickness of the first functional layer is 7-11 nm. The advantage of adopting this preferred embodiment is that both the reaction rate and the reaction heat effect can be taken into account at the same time.
[0033] In the present invention, preferably, based on the inner surface area of the hollow fiber membrane matrix per square meter of dry basis, the content of phenoxy in the first ene-philic layer is 14-30 mmol / m 2 The advantage of adopting this preferred embodiment is that the olefins in the raw material crude olefins can be captured and enriched.
[0034] In the present invention, preferably, the thickness of the first ene-philic layer is 4-6 nm. The advantage of adopting this preferred embodiment is that olefin enrichment and mass transfer can be taken into account, thereby improving reaction performance.
[0035] In the present invention, preferably, based on the surface area of the hollow fiber membrane substrate per square meter on a dry basis, the content of the amide group in the second functional layer is 18-35 mmol / m 2 The content of pyrrolyl is 13-21mmol / m 2 , the furanyl content is 2-5mmol / m 2 The advantage of adopting this preferred embodiment is that it can take into account both water enrichment and low-carbon alcohol separation.
[0036] In the present invention, preferably, the thickness of the second functional layer is 5-8 nm. The advantage of adopting this preferred embodiment is that it can take into account water enrichment, low-carbon alcohol separation and mass transfer resistance.
[0037] A second aspect of the present invention provides a method for preparing a low-carbon olefin hydrated fiber membrane, wherein the method comprises:
[0038] (1) performing a silanization treatment on the hollow fiber membrane substrate to obtain a silanized hollow fiber membrane;
[0039] (2) in the presence of a first functional component, subjecting the inner surface of the silanized hollow fiber membrane of step (1) to a first functional treatment, and then in the presence of a first enephilic component, subjecting the inner surface of the hollow fiber membrane after the first functional treatment to a first enephilic treatment to obtain a hollow fiber membrane after the first enephilic treatment;
[0040] (3) in the presence of a second functional component, subjecting the outer surface of the hollow fiber membrane after the first olefin treatment in step (2) to a second functional treatment to obtain a low-carbon olefin hydrate fiber membrane;
[0041] The first functional component contains an amide group, a phenoxy group, a sulfonic acid group, a phosphate group, a pyrrol group, and a furan group; the first enophilic component contains a phenoxy group; and the second functional component contains an amide group, a pyrrol group, and a furan group.
[0042] In the present invention, the type, material and characteristic parameters of the hollow fiber membrane substrate in step (1) have been described in the first aspect and will not be repeated here.
[0043] In the present invention, there is no particular limitation on the preparation method of the hollow fiber membrane substrate. For example, it can be prepared by the following method: first, a casting solution is prepared, and then a hollow fiber embryo is prepared by a spinning molding-phase transformation process, and then the hollow ceramic fiber is obtained by drying and calcining. The preparation conditions of the hollow ceramic fiber are as follows: polyethersulfone (average molecular weight of 1500-3800), N-methylpyrrolidone, ceramic precursor (silicon dioxide and / or aluminum oxide), polyvinylpyrrolidone K90, in a mass ratio of (9-18): (65-95): (170-330): (4-9), stirred at 75-95°C for 40-60 hours, and then allowed to stand for degassing for 7-12 hours to obtain a casting solution. The inner and outer gel baths of the spinneret are deionized water at 0-3°C, the inner diameter of the spinneret is 0.3-0.7 mm, the outer diameter is 1.3-2.7 mm, the flow rate of the casting liquid is 4-8 ml / min, the pressure of the casting liquid in the spinneret is 150-300 kPa (gauge pressure), the ambient temperature is 20-30°C, the ambient humidity is 45-60%, the casting liquid and the inner and outer gel baths undergo solvent exchange and phase separation solidification to form a hollow fiber blank. The hollow fiber membrane blank is washed 4-8 times with desalted water, dried with air at 20-30°C, then heated to 1600-1800°C by a program of 0.5-1°C / min, kept at a constant temperature for 4-8 hours, and then naturally cooled to 20-30°C to obtain a hollow ceramic fiber membrane matrix.
[0044] In the present invention, preferably, in step (1), the silanization treatment causes the inner surface and outer surface of the hollow fiber membrane to be coated with a first silane layer and a second silane layer, respectively, and the thickness of the first silane layer and the second silane layer are independently 5-8 nm.
[0045] In the present invention, there is no particular limitation on the method of silanization treatment, as long as the first silane layer and the second silane layer can be formed. Preferably, in step (1), the silanization treatment includes: contacting the silane reagent solution with the hollow fiber membrane substrate, and then drying and curing. In the present invention, there is no particular limitation on the method and conditions of contact. Preferably, the contact method is immersion, and the immersion time is 90-150 seconds. In the present invention, there is no particular limitation on the conditions of drying and curing. Preferably, the temperature is 100-120°C and the time is 30-60 minutes. In the present invention, preferably, the drying and curing is carried out under a protective atmosphere, preferably an inert atmosphere and / or nitrogen.
[0046] In the present invention, preferably, in step (1), the silane reagent solution is obtained by pre-hydrolyzing a silane reagent, water and a low-carbon alcohol. In the present invention, there is no particular limitation on the conditions for pre-hydrolysis, and preferably, the pre-hydrolysis time is 12-24 hours.
[0047] In the present invention, there is no particular limitation on the content of each component in the silane reagent solution, as long as the thickness requirements of the first silane layer and the second silane layer are met. Preferably, the volume ratio of silane reagent: water: low carbon alcohol is (1.7-3.8): (3-5): (90-96).
[0048] In the present invention, preferably, the pH value of the silane reagent solution is 7.4-8.3.
[0049] In the present invention, preferably, the silane reagent is selected from at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
[0050] In the present invention, there is no particular limitation on the specific type of low-carbon alcohol. Preferably, the low-carbon alcohol is anhydrous methanol and / or anhydrous ethanol.
[0051] In the present invention, preferably, the amount of the silane reagent solution used is such that the thickness of the first silane layer and the second silane layer are independently 5-8 nm.
[0052] In the present invention, preferably, in step (2), the first functional treatment makes the inner surface of the silanized hollow fiber membrane in step (1) coated with a first functional layer, and the first functional layer contains amide, phenoxy, sulfonic acid, phosphate, pyrrol and furan groups.
[0053] In the present invention, preferably, based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of the amide group in the first functional layer is 10-17 mmol / m 2 , the content of phenoxy group is 9-16mmol / m 2 The content of sulfonic acid group is 16-30mmol / m 2 The content of phosphate group is 7-15mmol / m 2 The content of pyrrolyl is 18-26mmol / m 2 The furanyl content is 3-7mmol / m 2 .
[0054] In the present invention, preferably, in step (2), the first ene-philic treatment causes the inner surface of the hollow fiber membrane after the first functional treatment to be coated with a first ene-philic layer, wherein the first ene-philic layer contains phenoxy groups.
[0055] In the present invention, preferably, based on the inner surface area of the hollow fiber membrane matrix per square meter of dry basis, the content of phenoxy in the first ene-philic layer is 14-30 mmol / m 2 .
[0056] In the present invention, there is no particular limitation on the manner of the first functional treatment. Preferably, in step (2), the first functional treatment comprises: contacting a solution containing the first functional component with the inner surface of the silanized hollow fiber membrane in step (1).
[0057] In the present invention, there is no particular limitation on the types of components in the solution containing the first functional component, as long as the requirements of the first functional layer are met. Preferably, in step (2), the solution containing the first functional component contains a first polyether, a first functional component, a first initiator and water.
[0058] In the present invention, there is no particular limitation on the content of each component in the solution containing the first functional component, as long as the requirements of the first functional layer are met. Preferably, in the solution containing the first functional component, the mass ratio of the first polyether: the first functional component: the first initiator: water is 100: (3.2-5.3): (0.2-0.6): (1-2).
[0059] In the present invention, preferably, the average molecular weight of the first polyether is 500-1000.
[0060] In the present invention, there is no particular limitation on the type of the first initiator. Preferably, the first initiator is selected from at least one of azo, organic peroxide, inorganic peroxide and redox initiators, more preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate and hydrogen peroxide, and even more preferably benzoyl peroxide.
[0061] In the present invention, preferably, the first functional component is provided by amide derivatives, phenoxy derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives.
[0062] In the present invention, preferably, in the solution containing the first functional component, the molar ratio of amide derivatives: phenoxy derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is (13-23): (12-21): (21-39): (9-20): (24-34): (4-9).
[0063] In the present invention, there is no particular limitation on the type of amide derivatives. Preferably, the amide group is provided by an amide derivative, and preferably the amide derivative is selected from at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide.
[0064] In the present invention, there is no particular limitation on the type of phenoxy derivatives. Preferably, the phenoxy group is provided by a phenoxy derivative, and preferably the phenoxy derivative is selected from at least one of 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether.
[0065] In the present invention, there is no particular limitation on the type of phosphoric acid derivatives. Preferably, the phosphoric acid derivative is selected from at least one of (2-fluoro-3,7-dimethylocta-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate.
[0066] In the present invention, there is no particular limitation on the type of sulfonic acid derivatives. Preferably, the sulfonic acid group is provided by a sulfonic acid derivative, and preferably the sulfonic acid derivative is selected from at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate.
[0067] In the present invention, there is no particular limitation on the type of pyrrole derivatives. Preferably, the pyrrole group is provided by a pyrrole derivative, and preferably the pyrrole derivative is selected from at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one.
[0068] In the present invention, there is no particular limitation on the type of furan derivatives. Preferably, the furanyl group is provided by a furan derivative, and preferably the furan derivative is 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan.
[0069] In the present invention, the inner cavity of the hollow fiber membrane is completely filled by the first functional treatment, so that the first polyether gel solution is only coated on the inner surface of the hollow fiber membrane and part of the pores close to the inner surface, and the outer surface is not coated. In the present invention, the conditions of the first functional treatment are not particularly limited. Preferably, in step (2), the conditions of the first functional treatment include: introducing a solution containing the first functional component into the inner cavity of the silanized hollow fiber membrane described in step (1), and the back pressure of the inner cavity outlet is 10-20 kg in terms of gauge pressure. Preferably, the first functional treatment also includes introducing the solution containing the first functional component and then treating it in a protective atmosphere (preferably nitrogen) at 80-100°C for 0.7-1.5 hours; after cooling to room temperature, soaking and washing with an organic solvent (preferably benzene) at 70-80°C for 4-8 times, and then drying in a nitrogen atmosphere. The first polyether gel is pressurized and pumped into the inner cavity of the hollow fiber membrane to completely fill the inner cavity and avoid coating the first functional component on the outer surface of the hollow fiber membrane. The first polyether is preferably removed by washing with benzene. This operation is simple and has low cost.
[0070] In the present invention, there is no particular limitation on the amount of the solution containing the first functional component. Preferably, the amount of the solution containing the first functional component is such that the thickness of the first functional layer of the prepared low-carbon olefin hydrated fiber membrane is 7-11 nm.
[0071] In the present invention, there is no particular limitation on the method of the first ene-philic treatment. Preferably, in step (2), the first ene-philic treatment comprises: contacting a solution containing the first ene-philic component with the inner surface of the hollow fiber membrane after the first functional treatment.
[0072] In the present invention, preferably, in step (2), the solution containing the first enophilic component contains the second polyether, the first enophilic component, the second initiator and water.
[0073] In the present invention, there is no particular limitation on the content of each component in the solution containing the first enophilic component. Preferably, in the solution containing the first enophilic component, the mass ratio of the second polyether: the first enophilic component: the second initiator: water is 100: (3.8-6.2): (0.3-0.6): (1-2).
[0074] In the present invention, the type of the second initiator is not particularly limited, and the second initiator may be the same as or different from the first initiator, but is preferably the same as the first initiator.
[0075] In the present invention, preferably, the average molecular weight of the second polyether is 800-2000.
[0076] In the present invention, preferably, the first enophilic component is provided by a phenoxy derivative, further preferably at least one selected from 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether.
[0077] In the present invention, the solution containing the first ene-philic component contains a second polyether, and the viscosity of the second polyether is greater than the viscosity of the first polyether. Therefore, the solution containing the first ene-philic treatment component cannot penetrate into the pores and is only used to modify the inner surface of the hollow fiber membrane substrate. The conditions for the first ene-philic treatment are not particularly limited in the present invention. Preferably, in step (2), the conditions for the first ene-philic treatment include: introducing the solution containing the first ene-philic component into the inner cavity of the hollow fiber membrane after the first functional treatment, and the back pressure of the inner cavity outlet is 6-13 kg in terms of gauge pressure. Preferably, the first ene-philic treatment also includes introducing the solution containing the first ene-philic component and then treating it under a protective atmosphere (preferably nitrogen) at 85-110°C for 0.8-1.5 hours, and cooling to room temperature. Preferably, the back pressure of the first ene-philic treatment is less than the back pressure of the first functional treatment.
[0078] In the present invention, there is no particular limitation on the amount of the solution containing the first ene-philic component. Preferably, the amount of the solution containing the first ene-philic component is such that the thickness of the first ene-philic layer of the prepared low-carbon olefin hydrated fiber membrane is 4-6 nm.
[0079] In the present invention, it can be understood that the first functional treatment and the first ene-philic treatment have respectively used the first polyether and the second polyether to fill the inner cavity of the hollow fiber membrane, and the inner cavity has been completely filled during the operation. Therefore, the first functional treatment and the first ene-philic treatment only mainly treat the inner surface part of the hollow fiber membrane, and the subsequent second functional treatment only treats the outer surface part of the hollow fiber membrane.
[0080] In the present invention, preferably, in step (2), the second functional treatment makes the outer surface of the hollow fiber membrane after the first ene-philic treatment coated with a second functional layer, and the second functional layer contains amide groups, pyrrol groups, and furan groups.
[0081] In the present invention, preferably, based on the surface area of the hollow fiber membrane substrate per square meter on a dry basis, the content of the amide group in the second functional layer is 18-35 mmol / m 2 The content of pyrrolyl is 13-21mmol / m 2 , the furanyl content is 2-5mmol / m 2 .
[0082] In the present invention, there is no particular limitation on the method of the second functional treatment. Preferably, in step (2), the second functional treatment comprises: contacting a solution containing the second functional component with the outer surface of the hollow fiber membrane after the first ene-philic treatment.
[0083] In the present invention, preferably, in step (3), the solution containing the second functional component contains the second functional component, a third initiator and a first solvent.
[0084] In the present invention, there is no particular limitation on the content of each component in the solution containing the second functional component. Preferably, in step (2), in the solution containing the second functional component, the mass ratio of the second functional component: the third initiator: the first solvent is (4.2-7.5): (0.1-0.4): (92-96).
[0085] In the present invention, there is no particular limitation on the type of the first solvent. Preferably, in step (2), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene.
[0086] In the present invention, the type of the third initiator is not particularly limited, and the third initiator may be the same as or different from the first initiator and the second initiator, but is preferably the same as the first initiator and the second initiator.
[0087] In the present invention, preferably, in step (2), the second functional component is provided by an amide derivative, a pyrrole derivative, or a furan derivative.
[0088] In the present invention, preferably, in the solution containing the second functional component, the molar ratio of amide derivatives: pyrrole derivatives: furan derivatives is (23-46): (16-28): (2-7).
[0089] In the present invention, amide derivatives, pyrrole derivatives and furan derivatives have been described in the above content and will not be described in detail here.
[0090] In the present invention, there is no particular limitation on the conditions for the second functional treatment, as long as the requirements of the second functional layer are met. Preferably, in step (3), the conditions for the second functional treatment include: a liquid-to-solid volume ratio of the solution containing the second functional component to the hollow fiber membrane after the first ene-phile treatment is 2-4, the soaking temperature is 60-80°C, and the time is 1.5-3h. Preferably, the second functional treatment also includes soaking and washing the soaked product in an organic solvent (preferably benzene) at 70-80°C for 4-8 times. The second polyether is removed by washing with an organic solvent.
[0091] In the present invention, there is no particular limitation on the amount of the solution containing the second functional component. Preferably, the amount of the solution containing the second functional component is such that the thickness of the second functional layer of the prepared low-carbon olefin hydrated fiber membrane is 5-8 nm.
[0092] In the present invention, preferably, step (3) further comprises post-treatment, and the post-treatment is carried out in the presence of a post-treatment agent. The advantages of adopting this preferred embodiment are to remove residual monomers and improve the pore structure.
[0093] In the present invention, there is no limitation on the specific operation mode of the post-treatment. Preferably, the post-treatment comprises soaking the second functional treatment product obtained by the second functional treatment in a post-treatment agent and then drying it.
[0094] In the present invention, there is no particular limitation on the type of post-treatment agent. Preferably, the post-treatment agent is selected from at least one of anhydrous ethanol, anhydrous acetone and anhydrous methanol, and more preferably anhydrous acetone.
[0095] In the present invention, there is no particular limitation on the post-treatment conditions. Preferably, the post-treatment conditions include: a soaking time of 0.5-1 h, a drying temperature of 120-150° C., and a drying time of 0.5-1 h.
[0096] The third aspect of the present invention provides a use of the light olefin hydrated fiber membrane described in the first aspect or the light olefin hydrated fiber membrane prepared by the preparation method described in the second aspect in a light olefin hydration reaction.
[0097] In the present invention, preferably, based on the total amount of olefin reaction raw materials, the content of light olefins in the olefin reaction raw materials for the light olefin hydration reaction is 10-100 volume %.
[0098] In the present invention, preferably, the low-carbon olefin is C3 and / or C4 olefin.
[0099] In the present invention, preferably, the low-carbon olefin hydration reaction comprises: olefin reaction raw materials and water are contacted with the inner and outer surfaces of the low-carbon olefin hydration fiber membrane respectively to carry out olefin hydration reaction to obtain an aqueous solution containing low-carbon alcohols.
[0100] In the present invention, there is no particular limitation on the equipment used for the olefin hydration reaction. Preferably, the olefin hydration reaction is carried out in an olefin hydration reactor, and it is further preferred to use an olefin hydration reactor with a shell-and-tube structure, and the low-carbon olefin hydration fiber membranes are arranged in parallel in the olefin hydration reactor. In the present invention, it is understood that water (preferably desalted water) flows through the shell side of the olefin hydration reactor (i.e., water contacts the outer surface of the hollow fiber membrane), and the low-carbon olefin flows through the tube side of the olefin hydration reactor (i.e., the low-carbon olefin contacts the inner surface of the hollow fiber membrane).
[0101] In the present invention, the conditions for the hydration reaction of low-carbon olefins can be selected in a wide range. Preferably, the conditions for the hydration reaction of low-carbon olefins include: a temperature of 80-150°C, a pressure of 500-2000 kPa on a gauge pressure, a molar ratio of water to low-carbon olefins of 1.5-4.5, and a processing capacity of olefin reaction raw materials of 520-860 L﹒ m2 based on the inner surface area of the hollow fiber membrane matrix on a dry basis. -2 ﹒h -1 .
[0102] In the present invention, preferably, the single-pass olefin conversion rate of olefin hydration is greater than 62%, and the low-carbon alcohol selectivity is greater than 95%.
[0103] The present invention will be described in detail below through examples.
[0104] In the present invention, the content of each group in the olefin hydration fiber membrane is measured by the above-mentioned test method.
[0105] In the present invention, component analysis adopts 20A high performance liquid chromatography system (Shimadzu Corporation, Japan, equipped with autosampler, 10AT and 10AD pumps, 20A multi-wavelength ultraviolet detector); ACQUITY UPLC / Xevo G2 QTOF ultra-high performance liquid chromatography high-resolution tandem mass spectrometry (Waters Corporation, USA, equipped with autosampler, diode array ultraviolet detector). High performance liquid chromatography conditions: chromatographic column: Zorbax Eclipse Plus C18 (4.6mm×150mm, 5μm), mobile phase: water (containing 0.06%v phosphoric acid): acetonitrile = 95:5, flow rate: 1.0mL / min, detection wavelength: 210nm, column temperature: 35°C, injection volume: 1μL. Ultra-high performance liquid chromatography conditions: chromatographic column: HSS T3 (2.1 mm × 100 mm, 1.7 μm); mobile phase: water, methanol; gradient elution (positive ion mode): 0 min V (water): V (methanol) = 85:15, 2.5 min later V (water): v (methanol) = 55:35, 4 min later V (water): V (methanol): 10:90, flow rate: 0.45 mL / min; gradient elution (negative ion mode): 0 min V (water): V (methanol): 70:30, 2.5 min later V (water): V (methanol) = 55:35, 3.5 min later V (water): V (methanol) = 10:90; flow rate: 0.45 mL / min; column temperature: 30 ° C; injection volume: 3 μL. Mass spectrometry conditions: electrospray ionization source (ESI), positive or negative ion scanning mode, capillary voltage 2 kV, cone voltage 30 eV, ion source temperature: 120 ° C, desolvation temperature 450 ° C, cone gas flow rate 50 L / h, desolvation gas (N2) flow rate 900 L / h.
[0106] Example 1
[0107] The composition of the olefin reaction raw materials in this embodiment, by volume percentage, includes: 33.1% isobutane, 8.5% normal butane, 56.7% normal butene, and 1.7% pentane.
[0108] The preparation method of the low-carbon olefin hydrated fiber membrane in this embodiment comprises: (1) performing silanization treatment on the inner and outer surfaces of the hollow fiber membrane substrate to obtain a silanized hollow fiber membrane; (2) performing a first functional treatment and a first olefin-philic treatment on the inner surface of the silanized hollow ceramic fiber membrane obtained in (1) in sequence, and then performing a second functional treatment on the outer surface to obtain a low-carbon olefin hydrated fiber membrane.
[0109] In this embodiment, the hollow fiber membrane matrix can be prepared by the following method: first prepare a casting solution, then prepare a hollow fiber embryo through a spinning molding-phase conversion process, and then dry and calcine to obtain a hollow ceramic fiber. The preparation conditions of the hollow ceramic fiber are as follows: polyethersulfone (average molecular weight of 2600), N-methylpyrrolidone, ceramic precursor (silicon dioxide), polyvinylpyrrolidone K90, according to the mass ratio of 13.5:80:250:6.5, stir at 85°C for 50 hours, then stand and degas for 9.5 hours to obtain a casting solution. The inner and outer gel baths of the spinneret are deionized water at 1.5°C, the inner diameter of the spinneret is 0.5 mm, the outer diameter is 2 mm, the casting solution flow rate is 6 ml / min, the casting solution pressure in the spinneret is 225 kPa (gauge pressure), the ambient temperature is 25°C, the ambient humidity is 52.5%, and the casting solution undergoes solvent exchange with the inner and outer gel baths and solidifies in phase separation to form a hollow fiber embryo. After the hollow fiber membrane embryo was washed with desalted water for 6 times, it was dried with air at 25°C, and then the temperature was raised to 1700°C at 0.7°C / min, kept constant for 6 hours, and then naturally cooled to 25°C to obtain the hollow ceramic fiber membrane matrix. The inner diameter of the hollow ceramic fiber is 0.3mm, the outer diameter is 1.3mm, the pore size of the fiber membrane wall is 55nm, and the porosity is 50%.
[0110] The hollow fiber membrane substrate is then contacted with the silane reagent solution, and then dried and cured to obtain a silanized hollow fiber membrane. The silane reagent solution is obtained by mixing a silane reagent, water and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 18 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 2.7:4:93. The pH value of the silane reagent solution is 7.8. The silane reagent is methylvinyldiethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The contact conditions are immersion, and the immersion time is 120 seconds. The drying and curing conditions are a temperature of 110°C, a time of 45 minutes, and a drying atmosphere of nitrogen. The amount of silane reagent solution used is such that the thickness of the first silane layer and the second silane layer are each independently 6.5 nm.
[0111] Subsequently, the inner surface of the silanized hollow fiber membrane is treated with a solution containing the first functional component to obtain a hollow fiber membrane after the first functional treatment. The solution containing the first functional component contains a first polyether, a first functional component, a first initiator, and water, wherein the mass ratio of the first polyether: the first functional component: the first initiator: water is 100:4.2:0.4:1.5. The average molecular weight of the first polyether is 750. The first initiator is benzoyl peroxide. The first functional component contains amide derivatives, phenoxy derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: phenoxy derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 18:16.5:30:14.5:29:6.5. The amide derivatives are provided by N,N-methylenebisacrylamide. The phenoxy derivatives are provided by allyl phenyl ether. The phosphate derivatives were provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivative is provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivative is provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furanyl is provided by 2-(1-propylene-2-yl)furan. The first functional treatment condition comprises: introducing a solution containing the first functional component into the inner cavity of the hollow fiber membrane after the silanization treatment in step (1), the back pressure of the inner cavity outlet is 15 kg, and then treating it in a nitrogen atmosphere at 90°C for 1.1 hours; after cooling to room temperature, washing it with hot benzene at 75°C for 6 times, and then drying it in a nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of amide groups in the first functional layer is 13.5 mmol / m 2 The content of phenoxyl groups is 12.4 mmol / m 2 The content of sulfonic acid group is 22.5mmol / m 2 The content of phosphate group is 10.9mmol / m 2 The content of pyrrolyl is 21.7mmol / m 2 The furanyl content is 4.9mmol / m 2 , the thickness of the first functional layer is 9 nm.
[0112] Subsequently, the first ene-philic component is used to perform the first ene-philic treatment on the inner surface of the hollow fiber membrane after the first functional treatment to obtain the hollow fiber membrane after the first ene-philic treatment. The solution of the first ene-philic component contains the second polyether, the first ene-philic component, the second initiator, and water, wherein the mass ratio of the second polyether: the first ene-philic component: the second initiator: the water is 100:5:0.45:1.5. The average molecular weight of the second polyether is 1500. The second initiator is benzoyl peroxide. The first ene-philic component is provided by a phenoxy derivative (allyl phenyl ether). The conditions for the first ene-philic treatment include: introducing the solution containing the first ene-philic component into the inner cavity of the hollow fiber membrane after the first functional treatment in step (2), the back pressure of the inner cavity outlet is 9.5 kg in terms of gauge pressure, and then treating it in a nitrogen atmosphere at 97°C for 1.1 hours; cooling to room temperature, and then drying in a nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of phenoxy in the first ene-philic layer is 22 mmol / m 2 , the thickness of the first enophilic layer is 5.1 nm.
[0113] Subsequently, the outer surface of the hollow fiber membrane after the first olefin treatment is subjected to a second functional treatment with a second functional component to obtain a low-carbon olefin hydrated fiber membrane. In the solution containing the second functional component, the mass ratio of the second functional component: the third initiator: the second solvent is 5.8:0.2:94. The second solvent is toluene. The second functional component contains amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: pyrrole derivatives: furan derivatives is 34.5:22:4.5. The amide derivatives are N,N-methylenebisacrylamide. The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivatives are provided by 2-(1-propylene-2-yl) furan. The second functional treatment conditions include: the liquid-to-solid volume ratio of the solution containing the second functional component to the hollow fiber membrane after the first olefin treatment is 3, the immersion temperature is 70°C, the time is 2.2h, and the immersion washing is performed 6 times with hot benzene at 75°C. The second functional treatment product is post-treated in a post-treatment agent. The post-treatment agent is anhydrous acetone. The post-treatment conditions include: immersion time of 0.7h, drying temperature of 135°C, and drying time of 0.7h. Based on the surface area of the hollow fiber membrane substrate per square meter of dry basis, the content of amide groups in the second functional layer is 26.5mmol / m 2 The content of pyrrolyl is 17mmol / m 2 , the furanyl content is 3.5mmol / m 2 , the thickness of the second functional layer is 6.4nm.
[0114] The prepared low-carbon olefin hydration fiber membrane is used in the hydration of low-carbon olefins. The olefin hydration fiber membranes are arranged in parallel in the olefin hydration reactor using a shell-and-tube structure. Olefins and desalted water are respectively in contact with the inner and outer surfaces of the low-carbon olefin hydration fiber membranes to carry out olefin hydration reactions to obtain aqueous solutions containing low-carbon alcohols. The conditions for the olefin hydration reaction include: a temperature of 115°C, a pressure of 1250 kPa on a gauge pressure, and a processing capacity of 687 L﹒ m2 of the inner surface area of the hollow fiber membrane matrix on a dry basis. -2 ﹒h -1 The molar ratio of water to low-carbon olefins is 3.1, the single-pass olefin conversion rate of olefin hydration is 68.4%, and the low-carbon alcohol selectivity is 97.6%.
[0115] Example 2
[0116] The same olefin reaction raw materials as in Example 1 were selected.
[0117] In this embodiment, the hollow fiber membrane matrix can be prepared by the following method: first prepare a casting solution, then prepare a hollow fiber embryo through a spinning molding-phase conversion process, and then dry and calcine to obtain a hollow ceramic fiber. The preparation conditions of the hollow ceramic fiber are as follows: polyethersulfone (average molecular weight of 1600), N-methylpyrrolidone, ceramic precursor (silicon dioxide), polyvinylpyrrolidone K90, according to the mass ratio of 10:68:320:5, stir at 94°C for 58 hours, then stand and degas for 11 hours to obtain a casting solution. The inner and outer gel baths of the spinneret are 0.5°C deionized water, the inner diameter of the spinneret is 0.4 mm, the outer diameter is 1.4 mm, the casting solution flow rate is 4.3 ml / min, the casting solution pressure in the spinneret is 155 kPa (gauge pressure), the ambient temperature is 23°C, the ambient humidity is 58%, and the casting solution undergoes solvent exchange with the inner and outer gel baths and solidifies in phase separation to form a hollow fiber embryo. After the hollow fiber membrane embryo was washed 8 times with desalted water, it was dried with air at 29°C, and then the temperature was raised to 1780°C at 0.6°C / min, kept constant for 7 hours, and then naturally cooled to 23°C to obtain the hollow ceramic fiber membrane matrix. The inner diameter of the hollow ceramic fiber is 0.2mm, the outer diameter is 1.2mm, the pore size of the fiber membrane wall is 35nm, and the porosity is 45%.
[0118] The hollow fiber membrane substrate is then contacted with the silane reagent solution, and then dried and cured to obtain a silanized hollow fiber membrane. The silane reagent solution is obtained by mixing a silane reagent, water and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 23 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 3.7:4.8:92. The pH value of the silane reagent solution is 8.1. The silane reagent is methylvinyldiethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The contact conditions are immersion, and the immersion time is 140 seconds. The drying and curing conditions are a temperature of 115°C, a time of 56 minutes, and a drying atmosphere of nitrogen. The amount of silane reagent solution used is such that the thickness of the first silane layer and the second silane layer are each independently 7.7nm.
[0119] Subsequently, the inner surface of the silanized hollow fiber membrane is treated with a solution containing the first functional component to obtain a hollow fiber membrane after the first functional treatment. The solution containing the first functional component contains a first polyether, a first functional component, a first initiator, and water, wherein the mass ratio of the first polyether: the first functional component: the first initiator: water is 100:5.2:0.5:1.8. The average molecular weight of the first polyether is 700. The first initiator is benzoyl peroxide. The first functional component contains amide derivatives, phenoxy derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: phenoxy derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 22:20:38:19:33:8. The amide derivatives are provided by N,N-methylenebisacrylamide. The phenoxy derivatives are provided by allyl phenyl ether. The phosphate derivatives were provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivative is provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivative is provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furanyl group is provided by a furan derivative, preferably 2-(1-propylene-2-yl)furan. The first functional treatment condition comprises: introducing a solution containing the first functional component into the inner cavity of the hollow fiber membrane after the silanization treatment in step (1), the back pressure of the inner cavity outlet is 18 kg based on the gauge pressure, and then treating it in a nitrogen atmosphere at 95°C for 1.4 hours; after cooling to room temperature, immersing and washing with hot benzene at 78°C for 7 times, and then drying in a nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of amide groups in the first functional layer is 16.3 mmol / m 2 The content of phenoxyl groups is 14.8 mmol / m 2 The content of sulfonic acid group is 28.1mmol / m 2 The content of phosphate group is 14.0mmol / m 2The content of pyrrolyl is 24.5mmol / m 2 The furanyl content is 5.9mmol / m 2 , the thickness of the first functional layer is 10 nm.
[0120] Subsequently, the first enephilic component is used to perform the first enephilic treatment on the inner surface of the hollow fiber membrane after the first functional treatment to obtain the hollow fiber membrane after the first enephilic treatment. The solution of the first enephilic component contains the second polyether, the first enephilic component, the second initiator, and water, wherein the mass ratio of the second polyether: the first enephilic component: the second initiator: the water is 100: 6.1: 0.5: 1.8. The average molecular weight of the second polyether is 1000. The second initiator is benzoyl peroxide. The first enephilic component is provided by a phenoxy derivative (allyl phenyl ether). The conditions for the first enephilic treatment include: introducing the solution containing the first enephilic component into the inner cavity of the hollow fiber membrane after the first functional treatment in step (2), the back pressure of the inner cavity outlet is 12 kg based on the gauge pressure, and then treating it under nitrogen atmosphere at 106°C for 1.4 hours; cooling to room temperature, and then drying in nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of phenoxy in the first enephilic layer is 28.6 mmol / m 2 , the thickness of the first enophilic layer is 5.8 nm.
[0121] Subsequently, the outer surface of the hollow fiber membrane after the first olefin treatment is subjected to a second functional treatment with a second functional component to obtain a low-carbon olefin hydrated fiber membrane. In the solution containing the second functional component, the mass ratio of the second functional component: the third initiator: the second solvent is 7.4:0.3:93. The second solvent is toluene. The second functional component contains amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: pyrrole derivatives: furan derivatives is 45:27:6. The amide derivatives are provided by N,N-methylenebisacrylamide. The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivatives are provided by 2-(1-propylene-2-yl) furan. The second functional treatment conditions include: the liquid-to-solid volume ratio of the solution containing the second functional component to the hollow fiber membrane after the first olefin treatment in step (2) is 4, the soaking temperature is 77°C, the time is 2.6h, and the solution is soaked and washed 7 times with hot benzene at 78°C. The second functional treatment product was post-treated in a post-treatment agent. The post-treatment agent was anhydrous acetone. The post-treatment conditions included: immersion time of 0.8 h, drying temperature of 146 ° C, and drying time of 0.8 h. Based on the surface area of the hollow fiber membrane substrate per square meter of dry basis, the content of amide groups in the second functional layer was 34.2 mmol / m 2 The content of pyrrolyl is 20.6mmol / m 2 The furanyl content is 4.5mmol / m2 , the thickness of the second functional layer is 7.7 nm.
[0122] According to the reaction method of Example 1, the conditions for the olefin hydration reaction include: a temperature of 90°C, a pressure of 800 kPa on a gauge pressure, a molar ratio of water to low-carbon olefin of 4.2, and a processing volume of olefin reaction raw materials of 550 L﹒ m2 based on the inner surface area of the hollow fiber membrane matrix on a dry basis. -2 ﹒h -1 The single-pass olefin conversion rate of olefin hydration is 73.5%, and the selectivity for low-carbon alcohols is 98.3%.
[0123] Example 3
[0124] The same olefin reaction raw materials as in Example 1 were selected.
[0125] In this embodiment, the hollow fiber membrane matrix can be prepared by the following method: first prepare a casting solution, then prepare a hollow fiber embryo through a spinning molding-phase conversion process, and then dry and calcine to obtain a hollow ceramic fiber. The preparation conditions of the hollow ceramic fiber are as follows: polyethersulfone (average molecular weight of 3700), N-methylpyrrolidone, ceramic precursor (silicon dioxide), polyvinylpyrrolidone K90, according to the mass ratio of 17:93:180:8, stir at 78°C for 43 hours, then stand and degas for 8 hours to obtain a casting solution. The inner and outer gel baths of the spinneret are deionized water at 2.5°C, the inner diameter of the spinneret is 0.6 mm, the outer diameter is 1.6 mm, the casting solution flow rate is 7.6 ml / min, the casting solution pressure in the spinneret is 280 kPa (gauge pressure), the ambient temperature is 27°C, the ambient humidity is 50%, and the casting solution undergoes solvent exchange with the inner and outer gel baths and solidifies in phase separation to form a hollow fiber embryo. After the hollow fiber membrane embryo was washed with desalted water for 5 times, it was dried with air at 23°C, and then the temperature was raised to 1650°C at 0.9°C / min, kept constant for 5 hours, and then naturally cooled to 27°C to obtain the hollow ceramic fiber membrane matrix. The inner diameter of the hollow ceramic fiber is 0.4mm, the outer diameter is 1.4mm, the pore size of the fiber membrane wall is 73nm, and the porosity is 56%.
[0126] The hollow fiber membrane substrate is then contacted with the silane reagent solution, and then dried and cured to obtain a silanized hollow fiber membrane. The silane reagent solution is obtained by mixing a silane reagent, water and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 14 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 1.8:3.2:94. The pH value of the silane reagent solution is 7.6. The silane reagent is methyl vinyl diethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The contact conditions are immersion, and the immersion time is 100 seconds. The drying and curing conditions are a temperature of 106°C, a time of 34 minutes, and a drying atmosphere of nitrogen. The amount of silane reagent solution used is such that the thickness of the first silane layer and the second silane layer are each independently 5.3 nm.
[0127] Subsequently, the inner surface of the silanized hollow fiber membrane is treated with a solution containing the first functional component to obtain a hollow fiber membrane after the first functional treatment. The solution containing the first functional component contains polyether, the first functional component, the first initiator, and water, wherein the mass ratio of the first polyether: the first functional component: the first initiator: the water is 100:3.6:0.3:1.3. The average molecular weight of the first polyether is 900. The first initiator is benzoyl peroxide. The first functional component contains amide derivatives, phenoxy derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: phenoxy derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 14:13:22:10:25:5. The amide derivatives are provided by N,N-methylenebisacrylamide. The phenoxy derivatives are provided by allyl phenyl ether. The phosphate derivatives were provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivative is provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivative is provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivative is provided by 2-(1-propylene-2-yl)furan. The first functional treatment condition comprises: introducing a solution containing the first functional component into the inner cavity of the hollow fiber membrane after the silanization treatment in step (1), the back pressure of the inner cavity outlet is 12 kg based on the gauge pressure, and then treating it in a nitrogen atmosphere at 83°C for 0.9 hours; after cooling to room temperature, immersing and washing it with hot benzene at 73°C for 5 times, and then drying it in a nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of amide groups in the first functional layer is 11.2 mmol / m 2 The content of phenoxyl groups is 10.3 mmol / m 2 The content of sulfonic acid group is 17.5mmol / m 2 The content of phosphate group is 7.9mmol / m 2The content of pyrrolyl is 20mmol / m 2 , the furanyl content is 4mmol / m 2 , the thickness of the first functional layer is 7.6 nm.
[0128] Subsequently, the first enephilic component is used to perform the first enephilic treatment on the inner surface of the hollow fiber membrane after the first functional treatment to obtain the hollow fiber membrane after the first enephilic treatment. The solution of the first enephilic component contains polyether, the first enephilic component, the second initiator, and water, wherein the mass ratio of the second polyether: the first enephilic component: the second initiator: the water is 100:3.9:0.4:1.2. The average molecular weight of the second polyether is 1800. The second initiator is benzoyl peroxide. The first enephilic component is provided by a phenoxy derivative (allyl phenyl ether). The conditions for the first enephilic treatment include: introducing the solution containing the first enephilic component into the inner cavity of the hollow fiber membrane after the first functional treatment in step (2), the back pressure of the inner cavity outlet is 8 kg based on the gauge pressure, and then treating it in a nitrogen atmosphere at 88°C for 0.9 hours; cooling to room temperature, and then drying in a nitrogen atmosphere. Based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of phenoxy in the first enephilic layer is 15.3 mmol / m 2 , the thickness of the first enophilic layer is 4.3 nm.
[0129] Subsequently, the outer surface of the hollow fiber membrane after the first olefin treatment is subjected to a second functional treatment with a second functional component to obtain a low-carbon olefin hydrated fiber membrane. In the solution containing the second functional component, the mass ratio of the second functional component: the third initiator: the second solvent is 4.3:0.2:95. The second solvent is toluene. The second functional component contains amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of amide derivatives: pyrrole derivatives: furan derivatives is 24:17:3. The amide derivatives are provided by N,N-methylenebisacrylamide. The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furanyl group is provided by the furan derivatives by 2-(1-propylene-2-yl) furan. The second functional treatment conditions include: the liquid-to-solid volume ratio of the solution containing the second functional component to the hollow fiber membrane after the first olefin treatment in step (2) is 3, the soaking temperature is 65°C, the time is 1.7h, and the solution is soaked and washed with hot benzene at 73°C for 5 times. The second functional treatment product is post-treated in a post-treatment agent. The post-treatment agent is anhydrous acetone. The post-treatment conditions include: immersion time of 0.7h, drying temperature of 131°C, and drying time of 0.7h. Based on the surface area of the hollow fiber membrane substrate per square meter of dry basis, the content of amide groups in the second functional layer is 19.5mmol / m 2 The content of pyrrolyl is 13.8mmol / m 2 The furanyl content is 2.43mmol / m2 , the thickness of the second functional layer is 5.3 nm.
[0130] According to the reaction method of Example 1, the conditions for the olefin hydration reaction include: a temperature of 140°C, a pressure of 1600 kPa on a gauge pressure, a molar ratio of water to low-carbon olefins of 1.8, and a processing volume of olefin reaction raw materials of 850 L﹒ m2 based on the inner surface area of the hollow fiber membrane matrix on a dry basis. -2 ﹒h -1 The single-pass olefin conversion rate of olefin hydration was 63.2%, and the selectivity for low-carbon alcohols was 96.3%.
[0131] Example 4
[0132] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 15.6% isobutane, 6.7% normal butane, 76.5% normal butene, and 1.2% pentane.
[0133] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 77.2%, and the selectivity of low-carbon alcohols was 98.5%.
[0134] Example 5
[0135] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 6.2% isobutane, 2.1% normal butane, 91.3% normal butene, and 0.4% pentane.
[0136] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 79.3%, and the selectivity of low-carbon alcohols was 98.7%.
[0137] Example 6
[0138] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 50.4% isobutane, 13.8% normal butane, 30.3% normal butene, and 5.5% pentane.
[0139] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 69.9%, and the selectivity of low-carbon alcohols was 98.1%.
[0140] Example 7
[0141] The method of Example 3 is followed, except that the product after the second functional treatment in this example is not post-treated with a post-treatment agent.
[0142] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 62.5%, and the selectivity of low-carbon alcohols was 95.2%.
[0143] Comparative Example 1
[0144] The same olefin reaction raw materials as those in Example 5 were selected, including, by volume percentage: 6.2% isobutane, 2.1% normal butane, 91.3% normal butene, and 0.4% pentane.
[0145] The olefin hydration reactor is filled with Suqing brand SQD-67 styrene macroporous strong acid cation exchange resin, the reaction temperature is 150℃, the reaction pressure is 75 kg, and the reaction mass space velocity is 1h -1 The single-pass conversion rate of n-butene is 11.32%, and the selectivity of low-carbon alcohols is 95.6%.
[0146] Comparative Example 2
[0147] The method of embodiment 3 is followed, except that only the first functional processing is performed.
[0148] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 32.3%, and the selectivity of low-carbon alcohols was 87.9%.
[0149] Comparative Example 3
[0150] The method of Example 3 is followed, except that the first ene treatment is not performed, and the other preparation steps and processes are the same as those of Example 3.
[0151] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 38.5%, and the selectivity of low-carbon alcohols was 88.2%.
[0152] Comparative Example 4
[0153] The method of Example 3 is followed, except that the second functional treatment is not performed, and the other preparation steps and processes are the same as Example 3.
[0154] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 39.6%, and the selectivity of low-carbon alcohols was 88.4%.
[0155] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A low-carbon olefin hydrated fiber membrane, characterized in that: The low-carbon olefin hydrated fiber membrane includes a hollow fiber membrane substrate, a first silane layer, a first functional layer and a first olefinic layer sequentially coated on the inner surface of the hollow fiber membrane substrate from the inside to the outside, and a second silane layer and a second functional layer sequentially coated on the outer surface of the hollow fiber membrane substrate from the inside to the outside; the first functional layer contains amide, phenoxy, sulfonic acid, phosphate, pyrrol and furan groups; the first olefinic layer contains phenoxy groups; the second functional layer contains amide, pyrrol and furan groups.
2. The low-carbon olefin hydrated fiber membrane according to claim 1, wherein: The hollow fiber membrane substrate is a hollow ceramic fiber membrane; And / or, the inner diameter of the hollow fiber membrane substrate is 0.1-0.5 mm, the outer diameter is 1.1-2.5 mm, the pore size of the fiber membrane wall is 30-80 nm, and the porosity is 40-60%; And / or, the hollow fiber membrane substrate is made of silicon dioxide and / or aluminum oxide.
3. The low-carbon olefin hydrated fiber membrane according to claim 1 or 2, wherein: The thickness of the first silane layer and the second silane layer are each independently 5-8 nm; And / or, the first silane layer and the second silane layer are each independently provided by at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
4. The low-carbon olefin hydrated fiber membrane according to any one of claims 1 to 3, wherein: Based on the inner surface area of the hollow fiber membrane matrix per square meter of dry basis, the content of amide groups in the first functional layer is 10-17 mmol / m 2 , the content of phenoxy group is 9-16mmol / m 2 The content of sulfonic acid group is 16-30mmol / m 2 The content of phosphate group is 7-15mmol / m 2 The content of pyrrolyl is 18-26mmol / m 2 The furanyl content is 3-7mmol / m 2 ; And / or, the thickness of the first functional layer is 7-11 nm.
5. The low-carbon olefin hydrated fiber membrane according to any one of claims 1 to 4, wherein: Based on the inner surface area of the hollow fiber membrane matrix per square meter of dry basis, the content of phenoxy in the first ene-philic layer is 14-30 mmol / m 2 ; And / or, the thickness of the first enophilic layer is 4-6 nm.
6. The low-carbon olefin hydrated fiber membrane according to any one of claims 1 to 5, wherein: Based on the surface area of the hollow fiber membrane substrate per square meter of dry basis, the content of amide groups in the second functional layer is 18-35 mmol / m 2 The content of pyrrolyl is 13-21mmol / m 2 , the furanyl content is 2-5mmol / m 2 ; Preferably, the thickness of the second functional layer is 5-8 nm.
7. A method for preparing a low-carbon olefin hydrate fiber membrane, wherein: The method includes: (1) performing a silanization treatment on the hollow fiber membrane substrate to obtain a silanized hollow fiber membrane; (2) in the presence of a first functional component, subjecting the inner surface of the silanized hollow fiber membrane of step (1) to a first functional treatment, and then in the presence of a first enephilic component, subjecting the inner surface of the hollow fiber membrane after the first functional treatment to a first enephilic treatment to obtain a hollow fiber membrane after the first enephilic treatment; (3) in the presence of a second functional component, subjecting the outer surface of the hollow fiber membrane after the first olefin treatment in step (2) to a second functional treatment to obtain a low-carbon olefin hydrate fiber membrane; The first functional component contains an amide group, a phenoxy group, a sulfonic acid group, a phosphate group, a pyrrol group, and a furan group; the first enophilic component contains a phenoxy group; and the second functional component contains an amide group, a pyrrol group, and a furan group.
8. The method according to claim 7, wherein: In step (1), the hollow fiber membrane substrate is a hollow ceramic fiber membrane; And / or, the inner diameter of the hollow fiber membrane substrate is 0.1-0.5 mm, the outer diameter is 1.1-2.5 mm, the pore size of the fiber membrane wall is 30-80 nm, and the porosity is 40-60%; And / or, the hollow fiber membrane substrate is made of silicon dioxide and / or aluminum oxide.
9. The method according to claim 7 or 8, wherein: In step (1), the silanization treatment causes the inner surface and the outer surface of the hollow fiber membrane to be coated with a first silane layer and a second silane layer, respectively, and the thickness of the first silane layer and the second silane layer are independently 5-8 nm; And / or, in step (1), the silanization treatment comprises: contacting a silane reagent solution with the hollow fiber membrane substrate, and then drying and curing; And / or, in step (1), the silane reagent solution is obtained by pre-hydrolysis of a silane reagent, water and a low-carbon alcohol; Preferably, the volume ratio of silane reagent: water: low carbon alcohol is (1.7-3.8): (3-5): (90-96); Preferably, the silane reagent is selected from at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
10. The method according to any one of claims 7 to 9, wherein: In step (2), the first functional treatment is performed so that the inner surface of the silanized hollow fiber membrane in step (1) is coated with a first functional layer, wherein the first functional layer contains an amide group, a phenoxy group, a sulfonic acid group, a phosphoric acid group, a pyrrolyl group, and a furanyl group; Preferably, based on the inner surface area of the hollow fiber membrane matrix per square meter on a dry basis, the content of amide groups in the first functional layer is 10-17 mmol / m 2 , the content of phenoxy group is 9-16mmol / m 2 The content of sulfonic acid group is 16-30mmol / m 2 The content of phosphate group is 7-15mmol / m 2 The content of pyrrolyl is 18-26mmol / m 2 The furanyl content is 3-7mmol / m 2 ; And / or, in step (2), the first ene-philic treatment causes the inner surface of the hollow fiber membrane after the first functional treatment to be coated with a first ene-philic layer, wherein the first ene-philic layer contains phenoxy groups; Preferably, based on the inner surface area of the hollow fiber membrane matrix on a dry basis per square meter, the content of phenoxy in the first ene-philic layer is 14-30 mmol / m 2 .
11. The method according to any one of claims 7 to 10, wherein: In step (2), the first functional treatment comprises: contacting a solution containing a first functional component with the inner surface of the silanized hollow fiber membrane in step (1); And / or, in step (2), the solution containing the first functional component contains a first polyether, a first functional component, a first initiator and water; and / or, in the solution containing the first functional component, the mass ratio of the first polyether: the first functional component: the first initiator: water is 100: (3.2-5.3): (0.2-0.6): (1-2); and / or, the average molecular weight of the first polyether is 500-1000; and / or, the first functional component is provided by amide derivatives, phenoxy derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives; Preferably, the molar ratio of amide derivatives: phenoxy derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is (13-23): (12-21): (21-39): (9-20): (24-34): (4-9); Preferably, the amide group is provided by an amide derivative, and preferably the amide derivative is selected from at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide; Preferably, the phenoxy group is provided by a phenoxy derivative, and preferably the phenoxy derivative is selected from at least one of 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether; Preferably, the phosphate group is provided by a phosphate derivative, and preferably the phosphate derivative is selected from at least one of (2-fluoro-3,7-dimethyloct-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate; Preferably, the sulfonic acid group is provided by a sulfonic acid derivative, preferably the sulfonic acid derivative is selected from at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate; Preferably, the pyrrole group is provided by a pyrrole derivative, preferably the pyrrole derivative is selected from at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one; Preferably, the furanyl group is provided by a furan derivative, preferably the furan derivative is 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan; And / or, in step (2), the conditions of the first functional treatment include: introducing a solution containing the first functional component into the inner cavity of the silanized hollow fiber membrane in step (1), and the back pressure at the outlet of the inner cavity is 10-20 kg in gauge pressure.
12. The method according to any one of claims 7 to 11, wherein: In step (2), the first enephilic treatment comprises: contacting a solution containing a first enephilic component with the inner surface of the hollow fiber membrane after the first functional treatment; And / or, in step (2), the solution containing the first enophilic component contains the second polyether, the first enophilic component, the second initiator and water; and / or, in the solution containing the first enephilic component, the mass ratio of the second polyether: the first enephilic component: the second initiator: water is 100: (3.8-6.2): (0.3-0.6): (1-2); and / or, the average molecular weight of the second polyether is 800-2000; And / or, the first enophilic component is provided by a phenoxy derivative, preferably at least one selected from 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether; And / or, in step (2), the conditions of the first ene-philic treatment include: introducing a solution containing the first ene-philic component into the inner cavity of the hollow fiber membrane after the first functional treatment, and the back pressure of the inner cavity outlet is 6-13 kg in terms of gauge pressure.
13. The method according to any one of claims 7 to 12, wherein: In step (3), the second functional treatment causes the outer surface of the hollow fiber membrane after the first ene-philic treatment to be coated with a second functional layer, wherein the second functional layer contains an amide group, a pyrrol group, and a furan group; And / or, based on the surface area of the hollow fiber membrane substrate on a dry basis per square meter, the content of amide groups in the second functional layer is 18-35 mmol / m 2 The content of pyrrolyl is 13-21mmol / m 2 , the furanyl content is 2-5mmol / m 2 .
14. The method according to any one of claims 7 to 13, wherein: In step (3), the second functional treatment comprises: contacting a solution containing a second functional component with the outer surface of the hollow fiber membrane after the first ene-philic treatment; And / or, in step (3), the solution containing the second functional component contains the second functional component, the third initiator and the first solvent; And / or, in step (3), in the solution containing the second functional component, the mass ratio of the second functional component: the third initiator: the first solvent is (4.2-7.5): (0.1-0.4): (92-96); and / or, in step (3), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, in step (3), the second functional component is provided by an amide derivative, a pyrrole derivative, or a furan derivative; Preferably, in the solution containing the second functional component, the molar ratio of amide derivatives: pyrrole derivatives: furan derivatives is (23-46): (16-28): (2-7); Preferably, in step (3), the conditions for the second functional treatment include: a liquid-to-solid volume ratio of the solution containing the second functional component to the hollow fiber membrane after the first ene-treatment is 2-4, the immersion temperature is 60-80°C, and the time is 1.5-3h.
15. The method according to claim 14, wherein: Step (3) further comprises post-treatment, wherein the post-treatment is carried out in the presence of a post-treatment agent; and / or, the post-treatment agent is selected from at least one of anhydrous ethanol, anhydrous acetone and anhydrous methanol, preferably anhydrous acetone; And / or, the post-treatment conditions include: soaking time of 0.5-1h, drying temperature of 120-150°C, and drying time of 0.5-1h.
16. Use of the light olefin hydrated fiber membrane according to any one of claims 1 to 6 or the light olefin hydrated fiber membrane obtained by the preparation method according to any one of claims 7 to 15 in a light olefin hydration reaction; Preferably, the raw materials for the hydration reaction of light olefins include: Olefin reaction raw materials and water; Preferably, based on the total amount of the olefin reaction raw material, the content of light olefins in the olefin reaction raw material is 10-100 volume %; Preferably, the light olefin is C3 and / or C4 olefin; Preferably, the light olefin hydration reaction comprises: bringing olefin reaction raw materials and water into contact with the inner surface and the outer surface of the light olefin hydration fiber membrane respectively to carry out a light olefin hydration reaction to obtain an aqueous solution containing light alcohol; Preferably, the conditions for the hydration reaction of light olefins include: temperature of 80-150°C, pressure of 500-2000 kPa, molar ratio of water to light olefins of 1.5-4.5, and olefin reaction raw material processing capacity of 520-860 L﹒ m2 based on the inner surface area of the hollow fiber membrane matrix on a dry basis. -2 ﹒h -1 .
Citation Information
Patent Citations
Hydrophilic membrane integrated olefin hydration process
CN104039435A
Pyrrolyl modification complex function polymeric adsorbent and manufacture method thereof
CN101245155A
Modified hollow ceramic fiber and preparation and application thereof
CN115957812A
Hollow Fiber Membrane and Method for Manufacturing Thereof
US20110031184A1
Cited By
Modified hydrolyzed filler, preparation method and application thereof, and preparation method of formaldehyde formic acid aqueous solution
CN117920341A
Modified hydrolyzed fillers, their preparation methods and applications, and methods for preparing formaldehyde-formic acid aqueous solutions.
CN117920341B